Synthesis and characterization of iridium/platinum-HZMS5 catalyst for isomerization of n-pentage [electronic resource] - Herma Dina Setiabudi, 1987- 547125
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2013